The role of social innovation in criminal justice reform and the risk posed by proposed reforms in England and Wales - Fox, Chris; Grimm, Robert (Criminology & Criminal Justice: An International Journal, 2015)
The UK government has called for a rehabilitation revolution in England and Wales and put its faith in market testing. It hopes this will lead to greater innovation, resulting in reductions in re-offending while also driving down costs. However, many of the most innovative developments in criminal justice over recent decades have come through social innovation. Examples include restorative justice and justice reinvestment. In this article we argue that while social innovation will respond to some extent to conventional economic policy levers such as market testing, de-regulation and the intelligent use of public sector purchasing power it is not simply an extension of the neo-liberal model into the social realm. Social innovation, based on solidarity and reciprocity, is an alternative to the logic of the neo-liberal paradigm. In policy terms, the promotion of social innovation will need to take account of the interplay between government policy, social and cultural norms and individual and social capacity. Current proposals for reforming the criminal justice system may not leave sufficient scope to develop the conditions for effective social innovation.
Number: 1
Keywords: Europe; Réservé UdeM